Efektivitas Penggunaan Media Gambar Dalam Meningkatkan Hafalan Mufrodat Siswa Kelas 4 MI Darut Taqwa Sengonagung Purwosari Pasuruan - Badrus Sholeh (Universitas Yudharta Pasuruan, 2017)
In a learning process, teacher should be knowing and understanding abaout teaching and learning media, so the purpose of teaching will be successfully effectively such as in choosing media as learning tools. Mastery of vocabulary with picture media as learning tools can make students easy to communicate, well, active, effective and can memorize studying fastly especially in teaching memorize vocabulary. The method of this rsearch is quantitative descriptive with percentage counting formula. The instrument used in data collection are picture about profesion and the result of the test from researcher. The result of this research are 1) applying picture media can improving student skill in memorize vocabulary Arabic for student in MI Darut Taqwa Sengonagung Purwosari Pasuruan 2) it is based on improving mark from pre-test to post-test especially in memorize Arabic vocabulary between teaching vocabulary with picture media or without picture media for MI Darut Taqwa Sengonagung Purwosari Pasuruan.